HUBUNGAN ASUPAN ZAT GIZI MAKRO DAN STATUS HIDRASI DENGAN TINGKAT KEBUGARAN ATLET SEPAK BOLA ACADEMY KWARTA PONDOK ROWO KECAMATAN PERCUT SEI TUAN - Ardhana Hijratur Rahman; Hardi Firmansyah; Esi Emilia; Juliarti; Fatma Tresno Ingtyas (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2025)
Macro-nutrient intake and hydration status are important points that need to be considered in helping improve an athlete’s performance. The aim of the study was to determine the relationship between macro-nutrient intake and hydration status with fitness level among players of the Kwarta Academy Pondok Rowo Percut Sei Tuan. This study used a cross-sectional design and employed purposive sampling, with a sample of 34 individuals. Data on macro-nutrient intake were obtained from 3×24-hour recalls: two days during training days, and one day during a rest day, while hydration status was measured using the PURI card (Periksa Urin Sendiri — “Self-Urine Test”), meaning urine was collected and then stained using the available colors. Fitness level data were obtained from VO₂max tests using the Multistage Fitness Test (MFT). Data analysis was performed using bivariate analysis (Chi-Square test) and multivariate analysis (binary logistic regression) with the Statistical Package for the Social Sciences (SPSS). The respondents mostly had insufficient carbohydrate intake (70.6%), sufficient protein intake (91.2%), insufficient fat intake (67.6%); the majority were dehydrated in terms of hydration status (61.8%); and fitness level was split equally between fit and not fit (50%). The bivariate analysis showed that carbohydrate intake (p = 0.000), fat intake (p = 0.010), and hydration status (p = 0.010) had a significant relationship with fitness level, since their p-values were < 0.05; meanwhile protein intake (p = 0.070) did not have a significant relationship with fitness level. The binary logistic regression analysis revealed a significant relationship between macro-nutrient intake and hydration status with fitness level. In other words, when macro-nutrient intake and hydration status decline, fitness level also decreases. The Nagelkerke R Square value was 0.741 — indicating that 74.1% of the variation in fitness level is explained by macro-nutrient intake and hydration status.